2019
DOI: 10.1177/2515816319889971
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of high-frequency transcranial magnetic stimulation on motor cortex areas as a migraine preventive treatment

Abstract: Background: The results of high-frequency repetitive transcranial magnetic stimulation (rTMS) over the dorsolateral prefrontal cortex for migraine have been inconsistent. However, high-frequency rTMS over the motor cortex is a treatment that may be effective in relieving symptoms of migraine with a low risk of side effects. Methods: A systematic review of high-frequency rTMS over the brain motor cortex areas in human participants was conducted to assess efficacy in treating migraine. Articles that were not loo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 88 publications
0
5
0
1
Order By: Relevance
“…Recent systematic reviews and meta-analyses have converged on the promising contribution of M1-rTMS in reducing headache frequency, intensity, duration, abortive medication use, and functional impairment in both episodic and chronic migraine [ 89 , 90 , 91 , 92 , 93 ]. The preferred TMS parameters in the meta-analysis of Moisset et al were high-frequency (10 Hz) rTMS applied over the left M1, with 600–3000 pulses per session, stimulation intensity at 70–80% RMT, and for 1–10 sessions [ 91 ].…”
Section: Painmentioning
confidence: 99%
“…Recent systematic reviews and meta-analyses have converged on the promising contribution of M1-rTMS in reducing headache frequency, intensity, duration, abortive medication use, and functional impairment in both episodic and chronic migraine [ 89 , 90 , 91 , 92 , 93 ]. The preferred TMS parameters in the meta-analysis of Moisset et al were high-frequency (10 Hz) rTMS applied over the left M1, with 600–3000 pulses per session, stimulation intensity at 70–80% RMT, and for 1–10 sessions [ 91 ].…”
Section: Painmentioning
confidence: 99%
“…Although demonstrating a good safety profile, rTMS remains investigational for pain disorder, post-traumatic headache, and primary headache disorders. Based on two recent systematic reviews, high-frequency rTMS over the motor cortex demonstrated efficacy as a migraine treatment, but further high-quality RCTs with a standardized protocol are required to validate a treatment effect [23,33].…”
Section: Repetitive Transcranial Magnetic Stimulationmentioning
confidence: 99%
“…Up to now, rTMS trials in CM-MOH have used activating high stimulation rates (10 or 20 Hz) and targeted either the dorsolateral prefrontal cortex (DLPFC) [19][20][21] or the primary motor cortex [22], yielding conflicting results [20,21,23]. A meta-analysis on the subject was published recently [24].…”
Section: Introductionmentioning
confidence: 99%